1976
DOI: 10.1139/z76-228
|View full text |Cite
|
Sign up to set email alerts
|

Cytology of the anterior pituitary at different times of the year in normal and methallibure-treated male Columbian black-tailed deer (Odocoileus hemionus columbianus)

Abstract: WEST, N. O., and H. C. NORDAN. 1976. Cytology of the anterior pituitary at different t~mes of the year in normal and methallibure-treated male Columbian black-tailed deer (Odocoileus hemionus columbianus). Can. J. Zool. 54: 1969-1978. The application of histochemical staining techniques to the anterior pituitary revealed the presence of seven cell types. Most cell types underwent cyclic changes that could be related to a seasonal pattern of functional activity. The cell type tentatively identified as the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Quantitative studies have shown that the thyrotrophs generally constitute a small proportion of the PD cells, 4–6% (Childs et al, 1983) and 2.09% (Dada et al, 1984) in rat, 1.36% in bat (Anthony and Gustafson, 1984), 0.43% in mouse (Messier, 1965), 5% in voles (Clarke and Forsyth, 1964), and 1% in black‐tailed deer (West and Nordan, 1976). In viscacha, the values observed were between 2.39% and 1.16% (summer–early autumn and winter, respectively), showing a similar proportion to that reported for other species.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative studies have shown that the thyrotrophs generally constitute a small proportion of the PD cells, 4–6% (Childs et al, 1983) and 2.09% (Dada et al, 1984) in rat, 1.36% in bat (Anthony and Gustafson, 1984), 0.43% in mouse (Messier, 1965), 5% in voles (Clarke and Forsyth, 1964), and 1% in black‐tailed deer (West and Nordan, 1976). In viscacha, the values observed were between 2.39% and 1.16% (summer–early autumn and winter, respectively), showing a similar proportion to that reported for other species.…”
Section: Discussionmentioning
confidence: 99%
“…The volume fraction of these cells in adult male rats has been estimated at 5% (Childs, 1983) and the numerical density in adult female rats at 2.6% to 3.5% (Poole and Kornegay, 1982). Thyrotropes constitute 0.43% of the cells of the pars distalis in mice (Messier, 19651, 5% in voles (Clarke and Forsyth, 1964), and 1 to 2% in black-tailed deer (West and Nordan, 1976).…”
Section: Distribution and Abundance Of Thyrotropesmentioning
confidence: 99%